2013
DOI: 10.1016/j.ijcard.2013.01.253
|View full text |Cite
|
Sign up to set email alerts
|

Long term quality-of-life in patients with bradycardia pacemaker implantation

Abstract: ClinicalTrials.gov Identifier: NCT00135174; http://www.clinicaltrials.gov/ct2/show/NCT00135174.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
0
15

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 36 publications
6
47
0
15
Order By: Relevance
“…The primary hypothesis that a telephone‐based peer support combined with face‐to‐face group sessions would significantly improve postoperative health‐related quality of life was not supported. We observed significant improvement in patients' quality of life after implantation in both groups, which was consistent with other studies (Lopez‐Villegas et al, ; Udo et al, ). However, we found that peer support was effective in improving patients' negative emotions.…”
Section: Discussionsupporting
confidence: 92%
“…The primary hypothesis that a telephone‐based peer support combined with face‐to‐face group sessions would significantly improve postoperative health‐related quality of life was not supported. We observed significant improvement in patients' quality of life after implantation in both groups, which was consistent with other studies (Lopez‐Villegas et al, ; Udo et al, ). However, we found that peer support was effective in improving patients' negative emotions.…”
Section: Discussionsupporting
confidence: 92%
“…Nonetheless, TPS performed better than conventional VVIR PM on the general health score that showed little or no improvement for conventional VVIR PM at 3 and 12 months. Similar trends in HRQoL scores were reported in FOLLOWPACE, a prospective observational study of traditional PM outcomes in a Dutch population …”
Section: Discussionsupporting
confidence: 80%
“…This would account for the lower proportion of age-stratified deaths from cancer, stroke and dementia than observed at the national level, albeit on low numbers of patients. Although medical interventions become more complicated and expensive in patients with limited LE due to advanced age [8,18], the oldest patients, in particular, may benefit from improvements in mobility, cognitive function, and activities of daily living [20,21]. Increasing LE and longer follow-up, even for older patients, has been associated with relatively low costs [22], making advanced age alone no argument for not implanting a PPM if indicated.…”
Section: Discussionmentioning
confidence: 99%
“…No adjustment to EYLL for disability was required, as implantation of a pacemaker is generally associated with improved quality of life and health values [20,21].…”
Section: Strengths and Limitationsmentioning
confidence: 99%